2012
DOI: 10.1177/193229681200600216
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Modified Needle Tip Geometry on Penetration Force as Well as Acceptability, Preference, and Perceived Pain in Subjects with Diabetes

Abstract: Background:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 24 publications
3
71
0
Order By: Relevance
“…Use of either prefilled disposable or reusable pens can overcome some of the patient challenges to initiation of insulin therapy and may improve patient adherence and, possibly, patient outcomes 76. A study comparing a modified five-bevel needle pen tip (available globally since 2005) with that of a marketed three-bevel needle pen tip showed that pen geometry affects the penetrating force and, consequently, patient preferences 73. Moreover, compared to vials and syringes, insulin pens are preferred because they are easy to use, convenient, and deliver a precise and controlled amount of insulin 115.…”
Section: Resultsmentioning
confidence: 99%
“…Use of either prefilled disposable or reusable pens can overcome some of the patient challenges to initiation of insulin therapy and may improve patient adherence and, possibly, patient outcomes 76. A study comparing a modified five-bevel needle pen tip (available globally since 2005) with that of a marketed three-bevel needle pen tip showed that pen geometry affects the penetrating force and, consequently, patient preferences 73. Moreover, compared to vials and syringes, insulin pens are preferred because they are easy to use, convenient, and deliver a precise and controlled amount of insulin 115.…”
Section: Resultsmentioning
confidence: 99%
“…53 Patients also found the five-bevel less painful, but the difference did not reach statistical significance. Very recently, Hirsch et al 54 studied needles from several manufacturers in several gauges, ranging from 30-gauge to 32-gauge, to compare a new five-bevel needle tip to the standard three-bevel design. Penetration force during computer-controlled insertions using a human skin substitute was 23.7% less using a five-bevel tip versus matched needles with a three-bevel tip.…”
Section: Aronsonmentioning
confidence: 99%
“…An in vitro study comparing trifacet and pentafacet hypodermic needles demonstrated that the bevel geometry has a direct relation with the strength necessary for the penetration of needles into an artificial substitute of human skin (19) . Thus, the theory that seems to thrive is that of needles change between preparation and subcutaneous drug administration, as a way of guaranteeing the morphology of the bevels, can have a positive influence on the perception of discomfort in patients who use drugs through this route.…”
Section: Discussionmentioning
confidence: 99%